High intensity interval training on physical fitness - S, Adi; Aliriad, Hilmy; Arbanisa, Wahyu; Winoto, Ahmad; Ramadhan, Indra; Rizqanada, Ayutisa (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
physical performance, and sports. This article examines the research on high intensity interval training. This article aims to determine the effectiveness of high-intensity interval training on fitness and endurance. Data sources were taken from Scholar, Scimago Jr., Wiley Online Library, Springer. Search data ranges from 2015 to 2023. The method of implementing activities uses the literature review method. In this article, it is recommended that high intensity interval training should be done regularly with the right intensity and sufficient duration to achieve optimal results. The results of the review concluded that high intensity interval training can be done outside or inside the house which is suitable for athletes and non-athletes because it can increase muscle strength, reduce high blood pressure, improve cardiorespiratory fitness, burn fat, and help cure diabetes. In conclusion, high intensity interval training has an influence on changes in improving performance, health, and endurance. This strength training can further be developed or tested with various variables, subject characteristics, and a larger population. HIIT exercise can greatly increase physical performance. Optimal physical ability is intended to increase the body's metabolic system, cardiovascular fitness, and endurance, as well as influence health levels. HIIT is a quick and effective exercise that can be done both indoors and outdoors.Key words: high intensity interval training, physical fitness, endurance